Evaluation the effect of cultivated land protection policies based on the cloud model: A case study of Xingning, China. (November 2021) - Lu, Xinhai; Zhang, Yanwei; Zou, Yucheng
Highlights: The effects of cultivated land protection policies in different periods are compared. Comprehensively considering the 12 factors affecting the CLPP. The AHP-Entropy method was proposed to construct the cloud model of weight. A normal cloud model was established. An application for assessing the CLPP was developed by using the cloud model. Abstract: The evaluation of the effects of cultivated land protection policies (CLPP) is an important issue in China's food security and land policy regulation. This article first analyzes the historical evolution of CLPP in China and divides it into five stages. Based on this, this paper proposes a CLPP implementation effect evaluation framework based on the perspective of farmers' perception. Taking Xingning City, Guangdong Province as the research area, the AHP-entropy method and cloud model are used to evaluate the regional CLPP implementation effect. Results show that the comprehensive effect of CLPP is between "middle" and "good, " and specifically close to the "good" level. After the implementation of CLPP, its ecological management and protection, agricultural production enthusiasm, and farmers' satisfaction levels are generally at a medium or low level, and only the amount of cultivated land protection is at a medium to high level. Therefore, the formulation of CLPP in the future needs to start from the perspective of improving the comprehensive interests of farmers and enhance the focalization of policies. The cloud model realizes the uncertainty mapping of each evaluation index, takes into account the randomness and ambiguity of evaluation index quantification and grade division, and makes the evaluation result objective. This research method can serve as a reference for relevant land use policy evaluation.